Multiple Small RNAs Interact to Co-regulate Ethanol Tolerance in Zymomonas mobilis - Han, Runhua; Haning, Katie; Gonzalez-Rivera, Juan C.; Yang, Yongfu; Li, Runxia; Cho, Seung Hee; Huang, Ju; Simonsen, Bobi A.; Yang, Shihui; Contreras, Lydia M. (Frontiers in Bioengineering and Biotechnology, 2020)
sRNAs represent a powerful class of regulators that influences multiple mRNA targets in response to environmental changes. However, very few direct sRNA-sRNA interactions have been deeply studied in any organism. Zymomonas mobilis is a bacterium with unique ethanol-producing metabolic pathways in which multiple small RNAs (sRNAs) have recently been identified, some of which show differential expression in ethanol stress. In this study, we show that two sRNAs (Zms4 and Zms6) are upregulated under ethanol stress and have significant impacts on ethanol tolerance and production in Z. mobilis. We conducted multi-omics analysis (combining transcriptomics and sRNA-immunoprecipitation) to map gene networks under the influence of their regulation. We confirmed that Zms4 and Zms6 bind multiple RNA targets and regulate their expressions, influencing many downstream pathways important to ethanol tolerance and production. In particular, Zms4 and Zms6 interact with each other as well as many other sRNAs, forming a novel sRNA-sRNA direct interaction network. This study thus uncovers a sRNA network that co-orchestrates multiple ethanol related pathways through a diverse set of mRNA targets and a large number of sRNAs. To our knowledge, this study represents one of the largest sRNA-sRNA direct interactions uncovered so far.